2013
DOI: 10.3791/50265
|View full text |Cite
|
Sign up to set email alerts
|

Murine Model of Wound Healing

Abstract: Wound healing and repair are the most complex biological processes that occur in human life. After injury, multiple biological pathways become activated. Impaired wound healing, which occurs in diabetic patients for example, can lead to severe unfavorable outcomes such as amputation. There is, therefore, an increasing impetus to develop novel agents that promote wound repair. The testing of these has been limited to large animal models such as swine, which are often impractical. Mice represent the ideal precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 12 publications
1
139
0
4
Order By: Relevance
“…Long-term (23 DPA) exposure to 10 µM mubritinib induced contraction of the wound epidermis, similar to that observed in mice after injury (Dunn et al, 2013), in contrast to the minimal wound contraction observed in control limbs (Fig. 3K,L).…”
Section: Nrg1 Supplementation Rescues Regeneration In Denervated Limbssupporting
confidence: 81%
“…Long-term (23 DPA) exposure to 10 µM mubritinib induced contraction of the wound epidermis, similar to that observed in mice after injury (Dunn et al, 2013), in contrast to the minimal wound contraction observed in control limbs (Fig. 3K,L).…”
Section: Nrg1 Supplementation Rescues Regeneration In Denervated Limbssupporting
confidence: 81%
“…However, wound healing in rodent models is fundamentally different to that in humans. This is because the major mechanism of wound closure is contraction, whereas in humans re-epithelialization and granulation tissue formation are the main means of healing (6,7). In addition, the porcine cutaneous wound healing model is frequently used as a model for human cutaneous wound healing (8).…”
Section: Animal Models Of Wound Healingmentioning
confidence: 99%
“…The use of experimental animals is highly crucial biological tools in human and veterinary medicine and it seems to remain reliable option as it was. Rodents are mostly chosen as experimental animals for acute and chronic wound model because their care and feeding are easy, they reproduce and grow quickly and their biological characteristics are well understood [3][4][5]11,12] . On the other hand, they create a significant problem during experimental studies in wound healing due to a loose connection between skin and subcutaneous tissues in these highly thin-skinned animals.…”
Section: Discussionmentioning
confidence: 99%
“…In human and veterinary medicine, experimental studies on animal models are widely used as an important biological approach to clarify the pathophysiology of wound healing and to identify new strategies [3,4] . Even if different animal species are used for this purpose, mice and other rodents are extensively preferred because their care and feeding are easy, they reproduce and grow quickly, suitable for application of surgical procedures and their biology is thoroughly investigated [3,5] . On the other hand, an excessive skin contraction is a reality and edges of the wound move rapidly towards the centre.…”
Section: Introductionmentioning
confidence: 99%